Perceptions of Secondary Level Students toward Causes and Consequences of Bullying - Singh, Shweta; Singh, Seema (JOURNAL OF INDIAN EDUCATION, 2023)
The study aims to investigate the perceived causes and consequences of bullying among secondary-level students. Bullying is defined as the intentional and repeated negative behaviour directed towards individuals who are unable to defend themselves (Olweus, 1994). A qualitative survey approach was employed to gather data, utilising a semi-structured interview schedule. Thematic analysis was conducted to analyse the collected data. The findings of the study indicate that students perceive various factors as the major causes of bullying, including financial conditions, physical appearance, being different from others, seeking enjoyment from the pain others, displaying aggression, seeking revenge, exerting power, experiencing jealousy, and engaging in frequent use of social networking sites and sharing passwords with others. Additionally, students perceive several consequences resulting from bullying, such as, school absenteeism, dropout rates, academic underachievement, anxiety, stress, depression, decreased self-confidence, aggressive behavior, feelings of loneliness, and even suicidal tendencies. These results shed light on the significant impact of bullying on students’ well-being and emphasise the need for interventions to address and prevent bullying in educational settings.